2009
DOI: 10.1179/174313208x327982
|View full text |Cite
|
Sign up to set email alerts
|

Local mild hypothermia induced by intra-arterial cold saline infusion prolongs the time window of onset of reperfusion injury after transient focal ischemia in rats

Abstract: Local cold saline infusion to the ischemic territory before reperfusion can lead to mild hypothermia of the ischemic territory and can prolong the therapeutic time window of reperfusion from 2 to 2.5 hours. Refinements of the cooling process, optimal target temperature, duration of the therapy and most importantly, clinical efficacy, require further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 18 publications
3
17
0
Order By: Relevance
“…Consistent with previous findings (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Luan et al, 2004;Zhao et al, 2009), we also clarified that transarterial regional hypothermia exerts strong neuroprotective effects on ischemia-reperfusion (I/R) injury (Kurisu et al, 2015). However, the effects of this therapy have only been examined in a typical ischemic stroke model, the transient middle cerebral artery occlusion (tMCAO) model (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Kurisu et al, 2015;Luan et al, 2004;Zhao et al, 2009), which is a complete reperfusion model (Fluri et al, 2015;Takahashi et al, 2012;Zhao and Steinberg, 2011). The effects of this therapy have not yet been investigated in other ischemic stroke models, even though ischemic stroke in humans is extremely diverse in its pattern of occlusion and reperfusion in actual clinical settings.…”
Section: Introductionsupporting
confidence: 82%
See 2 more Smart Citations
“…Consistent with previous findings (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Luan et al, 2004;Zhao et al, 2009), we also clarified that transarterial regional hypothermia exerts strong neuroprotective effects on ischemia-reperfusion (I/R) injury (Kurisu et al, 2015). However, the effects of this therapy have only been examined in a typical ischemic stroke model, the transient middle cerebral artery occlusion (tMCAO) model (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Kurisu et al, 2015;Luan et al, 2004;Zhao et al, 2009), which is a complete reperfusion model (Fluri et al, 2015;Takahashi et al, 2012;Zhao and Steinberg, 2011). The effects of this therapy have not yet been investigated in other ischemic stroke models, even though ischemic stroke in humans is extremely diverse in its pattern of occlusion and reperfusion in actual clinical settings.…”
Section: Introductionsupporting
confidence: 82%
“…The present study demonstrated that transarterial regional hypothermia exerts robust neuroprotective effects in the pMCAO with tCHP model, as well as the typical tMCAO model, as reported previously (Chen et al, 2013;Ding et al, 2003;Ding et al, 2004a;Ding et al, 2004b;Kurisu et al, 2015;Luan et al, 2004;Zhao et al, 2009). This therapy significantly improved neurological deficits and decreased infarct/edema volumes.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…However in the present study we demonstrated that treatment with 4°C HRSS and 24°C HRSS significantly reduced ALT and AST level compared with the I/R injury group and no significant attenuate was seen after only hypothermic normal saline administration. Zhao et al indicated that Hypothermia could change various pathways involved in the pathogenic effects of cerebral ischemia, including reductions in metabolic and enzymatic activity, glutamate release and re-uptake, inflammation, reactive oxidant production, vascular permeability, blood-brain barrier disruption and the expression of a host of other genes (65).…”
Section: Discussionmentioning
confidence: 99%
“…Brain temperature can be lowered by intra-arterial local infusion of cold fluid into the ischemic zone via an intraluminal filament Luan et al, 2004;Zhao et al, 2009). Intra-arterial cold infusions (IACI) have long been used during surgical procedures to prevent ischemic brain injury (Matsuwaka et al, 1998).…”
Section: Intra-arterial Local Coolingmentioning
confidence: 99%